GRAVITY MODELING OF SUBSURFACE STRUCTURES AND RESERVOIR CHARACTERIZATION USING SEISMIC INVERSION IN THE NIAS BASIN - Wibowo, Ramadhana; Setiadi, Imam; Firdaus, Yulinar; Rahardiawan, Riza (Marine Geological Institute of Indonesia, 2024)
The development of interpretation techniques opens new exploration opportunities in the forearc basins of western Indonesia, such as the Nias Basin which show signs of oil and gas seepage. Gravity and seismic inversion analysis were used to look into the Nias Basin in order to evaluate its subsurface structure, the location of sedimentary sub-basins, and the possible presence of hydrocarbon reservoirs. After filtering the data for the Complete Bouguer Anomaly (CBA), a residual anomaly was obtained. This allowed for the quantitative interpretation of structures below the surface using 2D gravity forward modelling. Seismic and well data interpretation includes sensitivity analysis, a well-seismic tie, picking horizons, and acoustic impedance (AI) inversion. The residual gravity anomaly reveals eight sub-basin patterns spread out in the Nias Basin with a relative continuity direction of northwest-southeast following the lineaments of basement highs. The subsurface geological model identified four rock formations. From deepest to shallowest, these units are metamorphic bedrock (2.7 g/cc), Lelematua Formation (2.5 g/cc), Gomo Formation (2.4 g/cc), and Gunungsitoli Formation with an overlying alluvium (2.25 g/cc). Interpretation of well and seismic suggests a target zone at a 2,017 – 2,101 meters depth. Using a model-based hard constraint for AI inversion in this zone indicates possible carbonate reservoirs. Based on sensitivity analysis with an interval of 34,000 - 47,000 (ft/s)*(g/cc), an AI cutoff value of more than 34,000 (ft/s)*(g/cc) was obtained. The carbonate is estimated to be a tight carbonate in the limestone of the Gomo Formation.